Individual Health History, Body Mass Index, and Behavior as Causative Factors of Non-Communicable Diseases - Mugianti, Sri; Suprajitno, Suprajitno; Riyadi, Bastianus Doddy; Suyitno, Juin Hadi (Research and Community Service Unit, Poltekkes Kemenkes Kupang, 2023)
Microorganisms do not cause non-communicable diseases (NCDs) but tend to change in modern lifestyles that do not apply CERDIK. In past research, the risk of suffering from non-communicable diseases was influenced by behavior, which consisted of three domains, namely knowledge, attitudes, and actions, without considering other individual factors. This study aims to assess the influence of individual health history factors, BMI, and behavior. The design used is cross-sectional. A sample of 302 people aged 15-59 are at risk of NCD and often visit fast food restaurants. Sampling using cluster random sampling. The variables collected are individual health history, BMI, and behavior. Data collection was carried out from April to June 2023. The analysis carried out was descriptive and structural equation modeling using PLS (Partial Least Square) software. The influence of the individual health history factor is 0.116, the BMI factor is 0.277, and the behavioral factor is -0.107. The resulting formula is . This formula can be used as a method to calculate the individual risk of suffering from NCDs.